Assessing Debris Flow Risk at a Catchment Scale for an Economic Decision Based on the LiDAR DEM and Numerical Simulation - Tang, Yaming; Guo, Zizheng; Wu, Li; Hong, Bo; Feng, Wei; Su, Xiaohong; Li, Zhengguo; Zhu, Yuhang (Frontiers in Earth Science, 2022)
Various risk management measures have been applied to reduce risks associated with the debris flow; however, only a few studies have adopted the economic benefit to evaluate measure effectiveness. The present study sought to explore debris flow risks at a catchment scale and establish the appropriate risk-reducing measures. The Chengbei Gully debris flow in Shanxi province (China) was selected for the case study. High-resolution topographic data of the drainage basin were obtained using the airborne LiDAR technology. FLO-2D software was used to simulate the debris flow process to perform hazard zonation. Vulnerability was estimated based on the location of elements at risk within the hazard zones and the field survey. Several structural and non-structural measures for controlling risks were proposed based on the risk assessment results, and the benefit–cost ratio was used to analyze their effectiveness. The findings indicated that the rainfall event triggering the Chengbei Gully debris flow had an 80-year return period. The total risk under this rainfall condition was 2.3 × 105 $, which was an unacceptable level according to the criteria of tolerance risk. The findings showed that the engineering measure was the best mitigation approach for the Chengbei Gully debris flow with a benefit of 1.35 million $ and a benefit–cost ratio of 6.43.